Common causes of hair loss – clinical manifestations, trichoscopy and therapy. (8th January 2021) - Alessandrini, A.; Bruni, F.; Piraccini, B.M.; Starace, M.
Abstract: The field of hair disorders is constantly growing. The most important hair diseases are divided in non‐ cicatricial and cicatricial ones. Non‐cicatricial alopecia are more frequent than cicatricial alopecia. The first step is to obtain a good history and physical examination. Laboratory testing is often unnecessary, while trichoscopy is fundamental for all hair diseases. Scalp biopsy is strongly suggested in cicatricial alopecia and in doubtful cases. Androgenetic alopecia, alopecia areata, telogen effluvium, trichotillomania are common causes of non‐ cicatricial alopecia. Frontal fibrosing alopecia, discoid lupus erythematosus, lichen planopilaris, follicullitis decalvans are some of the most common forms of cicatricial hair loss. Many treatments are available, and a prompt diagnosis is very important for the prognosis.